2003
DOI: 10.1002/asna.200310162
|View full text |Cite
|
Sign up to set email alerts
|

Spot modelling of the flare M4.5 dwarf YZ CMi

Abstract: Abstract.We report on a photometric study of the flare M4.5 dwarf YZ CMi as based on photoelectric observations from the seasons 1972/73, 1979/80 and 1996/97. We suggest spot activity to explain the light and colour curves. Spots are generally 500K cooler than the surrounding photosphere and there are basically two solutions available for the observations: high latitude spot changing slightly basic properties such as radius and latitude or active near-equatorial (belt-like) centers represented by three spots. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
(9 reference statements)
3
13
1
Order By: Relevance
“…This small difference will arise due to the differing ratio of the Planck function of the spot and the star due to their different temperatures; however, this difference will be muted as we move into the near infrared. For instance, assuming that GJ 1214 has spots 500 K cooler -a value supposedly consistent with another M4.5 dwarf (Zboril et al 2003) -than GJ 1214's ∼3000 K effective temperature (Charbonneau et al 2009), the 2.0% variability due to rotational modulation in the MEarth bandpass (∼780 nm), will translate into 1.5%, and 1.0% variability in J-band and Ks-band, respectively. Assuming the unspotted transit depth is 1.350% in these bands then the maximum transit depths from unocculted spots, which would results from measurements at the minimum flux of the observed rotational modulation, would be 1.369% in J and 1.364% in Ks-band.…”
Section: Gj 1214b's Transit Depth In the Near-infraredmentioning
confidence: 97%
“…This small difference will arise due to the differing ratio of the Planck function of the spot and the star due to their different temperatures; however, this difference will be muted as we move into the near infrared. For instance, assuming that GJ 1214 has spots 500 K cooler -a value supposedly consistent with another M4.5 dwarf (Zboril et al 2003) -than GJ 1214's ∼3000 K effective temperature (Charbonneau et al 2009), the 2.0% variability due to rotational modulation in the MEarth bandpass (∼780 nm), will translate into 1.5%, and 1.0% variability in J-band and Ks-band, respectively. Assuming the unspotted transit depth is 1.350% in these bands then the maximum transit depths from unocculted spots, which would results from measurements at the minimum flux of the observed rotational modulation, would be 1.369% in J and 1.364% in Ks-band.…”
Section: Gj 1214b's Transit Depth In the Near-infraredmentioning
confidence: 97%
“…Bondar' et al (2019) found an activity cycle of 27.5 ± 2.0 yr, estimated from more than 80 years of archival photometric observations, with peak-to-peak variations of 0.2−0.3 mag. Estimations of the effective temperature of YZ CMi range from 3045 K (from synthetic spectra fitting; Rojas-Ayala et al 2012) to 3600 K (from spectral color indices; Zboril 2003).…”
Section: The Active Star Yz CMImentioning
confidence: 99%
“…For the Sun as a star, ΔT 500-600 K because sunspot irradiance is dominated by the penumbral regions (cf., e.g., Lanza et al 2004, and references therein). For a star with T = 3750 K, a spot temperature deficit ΔT ≥ 1500 K is required to produce a R s that is comparable to that of a planetary transit, which is also unlikely for such a cool star (see, e.g., Berdyugina 2005;Zboril 2003). …”
Section: Influence Of Stellar Activity On Stellar Colours and The Chamentioning
confidence: 99%